Educational Communication Strategy To Improve Competitiveness In The Era Of Technological Change And Globalization - Muhammad Alfi Alfaridli; Muslimah, Aidatum; Iqna’a, Faiq Julia; Baharun, Hasan (Journal of Education Management Research, 2024)
This study aims to examine the educational communication strategies employed by a single educational institution to enhance its competitiveness in the era of globalization and technological transformation. Utilizing a qualitative approach with a case study method, data were collected through semi-structured interviews, observations, and document analysis at one school in the Gending sub-district. The study's participants included the school principal, teachers, and parents. The findings reveal that the integration of digital technology, the strengthening of institutional branding, and multi-stakeholder collaboration play pivotal roles in fostering strong relationships with various stakeholders and enhancing the institution's positive image. The study underscores the importance of adopting more holistic and adaptive communication strategies to enable educational institutions to remain competitive on a global scale. Additionally, the findings offer valuable insights for education managers in developing communication strategies that are both effective and sustainable in the face of globalization’s challenges.